Methods for Surgical Targeting of the STN in Early-Stage Parkinson’s Disease - Camalier, C R.; Konrad, P E.; Kao, C C.; Remple, M R.; Davis, T L.; Hedera, P; Phibbs, F T.; Molinari, A L.; Neimat, J S.; Gill, C E.; Nasr, H M.; Charles, P D. (Frontiers in Neurology, 2014)
Patients with Parkinson’s disease experience progressive neurological decline, and future interventional therapies are thought to show most promise in early stages of the disease. There is much interest in therapies that target the subthalamic nucleus (STN) with surgical access. While locating STN in advanced disease patients (Hoehn-Yahr III or IV) is well understood and routinely performed at many centers in the context of deep brain stimulation surgery (DBS), the ability to identify this nucleus in early stage patients has not previously been explored in a sizeable cohort. We report surgical methods used to target the STN nucleus in fifteen patients with early Parkinson’s disease (Hoehn-Yahr II), using a combination of image guided surgery, microelectrode recordings and clinical responses to macrostimulation of the region surrounding the STN. Measures of electrophysiology (firing rates, root mean squared activity) have previously been found to be lower than in later stage patients, however, the patterns of electrophysiology seen and dopamimetic macrostimulation effects are qualitatively similar to those seen in advanced stages. Our experience with surgical implantation of Parkinson’s patients with minimal motor symptoms suggest that it remains possible to accurately target the STN in early stage Parkinson’s disease using traditional methods.